1998
DOI: 10.1183/09031936.98.12051079
|View full text |Cite
|
Sign up to set email alerts
|

Age-dependent inaccuracy of asthma death certification in Northern England, 1991-1992

Abstract: Asthma morbidity in England and Wales appears to have increased in recent decades, despite advances in therapy, and this is widely attributed to increasing asthma prevalence. This increase has not, however, been fully reflected by mortality trends, and in children and young adults, there have been no clear changes. In adults aged Š45 yrs (in whom >85% of current asthma deaths are recorded), mean annual mortality doubled between the mid1970s and the early 1990s in both sexes [1,2]. The rate of change and the de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 8 publications
0
16
0
1
Order By: Relevance
“…ROBERTS et al [26] noted a mortality of 2.25 per 100,000 in 1989 in females compared with 1.38 in males. Mortality data concerning asthma are, however, a further notorious source of inaccuracy [27]. If, nevertheless, there is an important sex anomaly concerning the clinical severity of asthma, the present findings may help to explain it.…”
Section: Discussionmentioning
confidence: 67%
“…ROBERTS et al [26] noted a mortality of 2.25 per 100,000 in 1989 in females compared with 1.38 in males. Mortality data concerning asthma are, however, a further notorious source of inaccuracy [27]. If, nevertheless, there is an important sex anomaly concerning the clinical severity of asthma, the present findings may help to explain it.…”
Section: Discussionmentioning
confidence: 67%
“…In eight studies panel members first assigned a cause of death independently, and the panel then jointly assessed cases in which the members had assigned different causes of death. Five studies used other methods to adjudicate differences between panel members: majority decision [13,21], decision by the panel chair [22], decision by an independent specialist [23], or excluding such deaths from the analysis [24]. In four papers, the panel procedures were not described.…”
Section: Review Procedures (Table 2)mentioning
confidence: 97%
“…It should be noted that "fatality" in this study is defined as that with its numerator determined by the number of asthmatic death for that year. It is impossible to distinguish the factors associated It has been reported that among elderly persons, the true asthma mortalities were overestimated 23,24). It is often difficult to distinguish between asthma and other obstructive respiratory diseases with asthma-like symptoms, especially in the very young and the elderly 23.25).…”
Section: Discussionmentioning
confidence: 99%